Presupposition And Entailment In "The Family Nightmare" Short Story - Zhafirah Hafizhah; Aura Syafira; Devi Oktaviani Putri; Emeliya Sukma Dara Damanik (Jurnal Pendidikan Indonesia, 2022)
The focus of this research is presupposition and entailment in The Familiy Nightmare short story. This research aimed to reveal how presupposition and entailment were used in the short story. This research used the qualitative method for analyzing the story which involved the document and material analysis to collecting the data. The result showed this research found 6 types of presuppositions and 2 types of entailments. Presupposition and entailment are to emphasize, draw attention, sympathy toward the readers, and become a strategy to make the readers more focused in the story.